Evaluasi Sistem Informasi Pendaftaran Dengan Metode Pieces Di Rumah Sakit TNI AD Dr. Soedjono Magelang - Wibawati, Savitri Anggita Cahya; , Yuli Kusumawati, SKM., M. Kes (Epid) (2017)
Minister of Health Regulation No. 82 Year 2013 on Hospital Management Information System (SIMRS), states that every hospital should implement management and development SIMRS. Registration Information System as part of SIMRS in medical records hospital dr. Soedjono Magelang in general have been carried out, but are still not optimal. This study aimed to analyze the implementation of the system of registration information in medical records hospital dr. Soedjono Magelang approach PIECES analysis (Performance, Information, Economic, Efficiency and Service). This study was an observational study descriptive qualitative method. Data were collected through observation, interview the officers Medical Record Unit and from secondary data support. The results showed the implementation of the information system of registration in dr. Soedjono Magelang in general has been running well since 2012 and revised in 2014. However the system is not optimal / maximum because the system has not been able to generate monthly reports automatically, so that based on the analysis method PIECES can be concluded that the implementation of information system of registration in the RS. Dr. Soejono Magelang been running 70%. `Keywords: Hospital, Hospital Management Information System (SIMRS), Registration Information System, Analysis PIECES